Juegos dramáticos y la socialización en niños de la institución educativa inicial N°386 Bellavista Callaru, Caballococha 2024 - Leon Farias, Claudina (2025)
The purpose of this study is to determine the relationship between the application of dramatic games and socialization in the children of the Institution Educative Indicial N°386 Bellavista Callaru Caballococha, 2024. This research has a quantitative approach and is developed under a non-involved research design. experimental, correlational and transactional. The study population was made up of a total of 139 children who belong to the aforementioned institution. For data collection, the observation technique was used, using a structured observation guide as an instrument. The validity of the instrument is guaranteed through an evaluation by a group of experts with experience in the area. As a result, a Kendall's Tau-b correlation coefficient of 0.641 was obtained, indicating a moderate and significant positive relationship between the application of dramatic games and children's socialization. The bilateral significance value obtained was 0.00, which is lower than the established significance threshold (p < 0.05), confirming the statistical relevance of the relationship between both variables.